Who is interested in what kind of sustainable development? Time-horizons and stakeholder interests - Joost Platje (Economic and Environmental Studies (E&ES), 2013)
While sustainable development is often interpreted as the need for a kind or harmonious development between its economic, social and environmental elements, this is unlike to be the case in reality. The author discusses the importance of knowledge and paradigms for establishing priorities in sustainable development. Then, the author reflects on the issue of the time aspect of sustainable development in a historical context, and the differences in priorities between different stakeholders. The differences in priorities and time horizons of stakeholders direct the issue towards the questions sustainability of what and who is interested in what kind of sustainable development.
Keywords: 330; sustainable development; stakeholder approach; education for sustainable development; time horizons; Development priorities